ANALYSIS OF CHANGES IN NURSE BEHAVIOR BEFORE AND AFTER PHLEBITIS PREVENTION TRAINING AT MEDAN BUNDA THAMRIN HOSPITAL IN 2019 - JETENDRA P SIHOMBING (JURNAL ILMIAH KOHESI, 2020)
Nosocomial infection is a serious problem that it can be a direct or indirect cause of patient’s death. Nurses play animportant role in infection control because nurses are health practitioners who deal directly with clients and infectiousmaterial in the ward. Phlebitis is one of nosocomial infection. The purpose study to determine the analysis of changes innurse behavior before and after phlebitis prevention training at Medan, Bunda Thamrin Hospital in 2019. Quasi Experimentstudy with a design of one group pre test and post test design used in this study. The sampling technique was randomsampling with a sample of 69 respondents. The research data was obtained by giving a test twice namely before being givenphlebitis prevention training and after phlebitis prevention training. Paired sample t test used to analize the data.The resultsshowed that there was an influence of behavior (knowledge) with a value of p = 0,000 (p <0.05), there was an influence ofbehavior (attitude) with a value of p = 0,000 (p <0.05), and there was influence of behavior (action ) with a value of p = 0,000(p <0.05). They showed that there are differences in nurse behavior before and after having phlebitis,prevention training atthe Bunda Thamrin Hospital in 2019. Hospitals need to hold phlebitis prevention training regularly and increase the fuction ofIPCLN by attending national training about PPI.